Toward a more inclusive history of the Cuban revolution of 1959. (1st December 2020) - Linger, Eloise
Abstract : The article claims that most historiography of the Cuban revolution of 1959 has omitted women, people of colour, and to some extent student youth and labourers. The shorter first part of the paper presents reasons of historical context and dominant Euro-male mindset that help explain why histories of Cuba's and other revolutions omitted women and people of colour until recent scholarship. Then, excerpts from oral testimonials of three activists in revolutionary movements of the 1950s give a livelier picture of how Afro-Cubans, women and youth provided the backbone and vast networks that kept alive and pushed forward the more highly celebrated guerrilla forces that came to power, led by Fidel Castro. Twentieth-century Cuban revolutionary context and continuity is evident in the quotes from Aida Pelayo, a leader of the civic coalition Mujeres Martianas in the 1950s, about her student days in the 1930s.